2018
DOI: 10.1186/s12886-018-0765-7
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in patients with corneal opacities

Abstract: BackgroundInvestigating the efficacy and safety of phacoemulsification with intraocular lens (IOL) implantation in corneal opacities.MethodsThis retrospective study was conducted in a tertiary medical center. Twenty-three eyes of 19 patients with cataracts and corneal opacities obscuring the pupillary center having received phacoemulsification with IOL insertion without any ancillary techniques were enrolled. The primary study outcome measures were uncorrected and best corrected visual acuity (BCVA), and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
10
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 31 publications
0
28
10
3
Order By: Relevance
“…In this study, postoperative UCVA (0.30 ± 0.17) and BCVA (0.22 ± 0.16) were significantly improved compared to preoperative UCVA (1.20 ± 0.34) and BCVA (1.10 ± 0.30) (P < 0.05). Ho et al reported preoperative mean UCVA and BCVA of 20/800 and 20/630, respectively, which significantly improved to 20/200 and 20/160 (P < 0.001) after cataract surgery with monofocal IOL implantation in patients with corneal opacity [4]. In the Ho et al's study, the amount of visual acuity improvement was less than that in our study, because astigmatism was not corrected in this study [4].…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…In this study, postoperative UCVA (0.30 ± 0.17) and BCVA (0.22 ± 0.16) were significantly improved compared to preoperative UCVA (1.20 ± 0.34) and BCVA (1.10 ± 0.30) (P < 0.05). Ho et al reported preoperative mean UCVA and BCVA of 20/800 and 20/630, respectively, which significantly improved to 20/200 and 20/160 (P < 0.001) after cataract surgery with monofocal IOL implantation in patients with corneal opacity [4]. In the Ho et al's study, the amount of visual acuity improvement was less than that in our study, because astigmatism was not corrected in this study [4].…”
Section: Discussioncontrasting
confidence: 66%
“…However, simultaneous penetrating keratoplasty and cataract surgery may induce more astigmatism than the preoperative condition [2,8]. Phacoemulsification and IOL implantation in selected cases of coexisting cataract and corneal opacity are safe and can provide suboptimal but long-term vision when penetrating keratoplasty is not an option or there is a high risk of graft failure [4]. Cataract surgery with toric IOL implantation could better improve visual acuity than simultaneous penetrating keratoplasty and cataract surgery when the central cornea is not totally opaque [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference was maintained throughout the follow up, from one month (mild haze) to the end of the study (12 months, full recovery of the Group 2) and it was significant starting from three months after PRK surgery. Moreover, no patient has developed corneal opacification, according to corneal opacification grading [23], in the following months.…”
Section: Resultsmentioning
confidence: 99%